Analisis Efisiensi Pemasaran Produk Spa yang Laris Terjual pada PT Bali Tangi - YULIASARI, NI KADEK WINDA; AMBARAWATI, I GUSTI AGUNG AYU; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.1, Januari 2018DO - 10.24843/JAA.2018.v07.i01.p07, 2018)
Marketing Efficiency Analysis of Best Seller Spa Products at PT Bali Tangi This research is aimed to find out the marketing channels, to calculate marketing margin, producer’s share, and to analyze marketing efficiency of best seller spa products at PT Bali Tangi. This company produces three types of spa products namely scrub, masker and massage oil that are in high demand. Samples were selected purposively for retailers from PT Bali and snowball sampling for retailers from the wholesaler. Total samples were 30 from Denpasar City and Badung Regency including wholesaler, retailers, hotels and villas. The results showed that there are three types of marketing channels of best seller spa products of PT Bali Tangi. Channel I: producer – end consumers (for three spa products), channel II: producer – retailers and institutional consumers – end consumers (for three spa products), and channel III: producer - wholesaler - institutional consumers – end consumers (for only two spa products). The channel II comprises 52.95% of the total sales, whereas 8.97% and 38.07% respectively for channel I and III. The highest marketing margin was seen from the channel III at amount of Rp 80,000/unit, while no marketing margin coming from the channel I as it is direct marketing. The channel II has marketing margin Rp 25,000. The highest producer’s share is on channel I by 100% and the lowest is on channel III by 57.89%. The channel II has producer’share of 86.49%. In terms of marketing efficiency, this research does not compare to channel I because channel I does not have a marketing agency. Channel II of the marketing channel is the most efficient based on three analysis of marketing margins, producer’s share, and price efficiency. Channel III is only efficient at operational efficiency of 2,944.57%. Meanwhile, channel III is inefficient. Despite of inefficiency, channel III is the main supporting channel for the company to maintain due to high volume of trading compared to channel I.